A Comparative Study on the Teaching Effects of TRIZ Courses for the Humanities - Lingling, LUO; Peng, LI; Ping, ZHANG (Asian Journal of Education and Training, 2017)
In order to test the feasibility of the curriculum system of TRIZ used in humanities and social science majors, this study will test whether it is effective to cultivate students’ creativity and to train their ability to solve problems. This study designs the randomly experimental targets in the two control groups for pretest and post-test. This study tests creative thinking and student self-evaluation questionnaire by use of the China Taiwan scholar, Wu Jingji’s design. The result indicates that the post-test, for the two groups of students, their creative thinking indicators have improved significantly. The results showed that TRIZ had a significant effect on improving students' creativity. Finally, this study has discussed the value of TRIZ Course contained in Humanities and Social Science Teaching and addressed the needs to improve.